Mutations in ADAR1, IFIH1, and RNASEH2B Presenting As Spastic Paraplegia - Crow, Yanick J.; Zaki, Maha S.; Abdel-Hamid, Mohamed S.; Abdel-Salam, Ghada; Boespflug-Tanguy, Odile; Cordeiro, Nuno J. V.; Gleeson, Joseph G.; Gowrinathan, Nirmala Rani; Laugel, Vincent; Renaldo, Florence; Rodriguez, Diana; Livingston, John H.; Rice, Gillian I. (Neuropediatrics, 2014)
Background Hereditary spastic paraplegia is a neurodegenerative phenotype characterized by a progressive loss of corticospinal motor tract function. In a majority of affected individuals the pathogenesis remains undetermined.Methods We identified a series of patients with a phenotype of nonsyndromic spastic paraplegia in whom no diagnosis had been reached before exome sequencing. We measured the expression of interferon stimulated genes (ISGs) in peripheral blood from these patients.Results Five patients from four families with previously unexplained spastic paraplegia were identified with mutations in either ADAR1 (one patient), IFIH1 (one patient), or RNASEH2B (three patients from two families). All patients were developmentally normal before the onset of features beginning in the second year of life. All patients remain of normal intellect. Four patients demonstrated normal neuroimaging, while a single patient had features of nonspecific dysmyelination. The patients with ADAR1 and IFIH1-related disease showed a robust interferon signature. The patients with mutations in RNASEH2B demonstrated no (two patients) or a minimal (one patient) upregulation of ISGs compared with controls.Conclusions Mutations in ADAR1, IFIH1, and RNASEH2B can cause a phenotype of spastic paraplegia with normal neuroimaging, or in association with nonspecific dysmyelination. Although the presence of an interferon signature can be helpful in interpreting the significance of gene variants in this context, patients with pathogenic mutations in RNASEH2B may demonstrate no upregulation of ISGs in peripheral blood. However, it remains possible that type I interferons act as a neurotoxin in the context of all genotypes.
Keywords: Aicardi–Goutières syndrome; spastic paraparesis; RNASEH2B; ADAR1; IFIH1; type I interferon; type I interferonopathy